When Debt spells Sin: Does Religiosity guard against Over-Indebtedness? - Konstantin Kiesel; Felix Noth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Over-indebtedness of individuals is attributed to unemployment, low education, financial illiteracy or age. We emphasize an additional determining factor: attitudes towards debt formed by religious beliefs. For Christians, debt is associated closely with guilt and sin yielding a negative "preconceived opinion" on debt. Yet, contrary to Catholicism, Protestant history and writings indicate also elements of a positive attitude towards debt. We hence test the effect of religious denomination on over-indebtedness using county-level data for Germany. To approach endogeneity, we apply the distance to important churches (Cathedrals, Dome, Münster) and historical events as instruments for a counties' percentage of Catholics and Protestants. We find that more widespread Catholicism in an area indeed leads to a lower share of over-indebted persons.
Keywords: D12; G11; Z12; 330